Profiling the barriers to the spreading of news using news headlines - Sittar, Abdul; Mladenić, Dunja; Grobelnik, Marko (Frontiers in Artificial Intelligence, 2023)
News headlines can be a good data source for detecting the barriers to the spreading of news in news media, which can be useful in many real-world applications. In this paper, we utilize semantic knowledge through the inference-based model COMET and the sentiments of news headlines for barrier classification. We consider five barriers, including cultural, economic, political, linguistic, and geographical, and different types of news headlines, including health, sports, science, recreation, games, homes, society, shopping, computers, and business. To that end, we collect and label the news headlines automatically for the barriers using the metadata of news publishers. Then, we utilize the extracted common-sense inferences and sentiments as features to detect the barriers to the spreading of news. We compare our approach to the classical text classification methods, deep learning, and transformer-based methods. The results show that 1) The inference-based semantic knowledge provides distinguishable inferences across the ten categories that can increase the effectiveness and enhance the speed of the classification model. 2) The news of positive sentiments cross the political barrier whereas the news of negative sentiments cross the cultural, economic, linguistic, and geographical barriers, 3) the proposed approach using inferences-based semantic knowledge and sentiment improves performance compare to using only headlines in barrier classification. Namely, the average F1-score for 4 out of 5 barriers has significantly improved as follows. For cultural barriers from 0.41 to 0.47, for economic barriers from 0.39 to 0.55, for political barriers from 0.59 to 0.70 and for geographical barriers from 0.59 to 0.76.